1967
DOI: 10.1002/1097-0142(1967)20:5<896::aid-cncr2820200551>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of radioactive cyclophosphamide.Animal tests and clinical studies

Abstract: This paper presents the results of animal tests and clinical studies on the metabolism of radioactive cyclophosphamide (Endoxan). The authors conclude that most of the metabolic breakdown of Endoxan occurs within the first two to three hours after administration. Further radiochromatographical investigations must be undertaken before the distribution of cytostatically active metabolites and their concentration in the tumor tissue can be elucidated. Studies on cerebral tumors have shown that the concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1970
1970
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This might be due to the presence of a very slowly exchange compartment. However, the present data are too few and previous studies (GRAUL et al 1967 have been of too short duration to allow any safe conclusions. Further studies with prolonged sampling are needed to elucidate these very important conditions.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This might be due to the presence of a very slowly exchange compartment. However, the present data are too few and previous studies (GRAUL et al 1967 have been of too short duration to allow any safe conclusions. Further studies with prolonged sampling are needed to elucidate these very important conditions.…”
Section: Discussionmentioning
confidence: 59%
“…Subsequently the concentra-tion of the metabolites increased steadily and after 2 days constituted nearly all the activity of the serum. In contrast to this only insignificant amounts of or no metabolites could be demonstrated in the serum in normal subjects some 12-24 hours after injection of cyclophosphamide (GRAUL et al 1967; DEVITA & ADAMSON 1970; BR~CK et al 1971; BAGLEY et al 1973; MOURID-SEN et al 1974).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This view would be reasonably understandable if the drug action of BLM as a cytostatic agent is considered, and would be supported by the observation that, with regard to meningioma, which is both an intracranial and an extracerebral tumour, higher concentration of BLM was found in the tumours showing histological malignancy. The second possible explanation is that the blood brain barrier in brain tumour tissue of higher malignancy might be more defective (Hossmann, 1967) and less limiting to drug entrance into the Graul et al (1967), who have made drug distribution studies using tritiated cyclophosphamide, suggested that the drug concentration in the tumour is largely dependent upon the blood supply to the tissue. If it is accepted that the tumour stain on cerebral angiography indicates abundant blood supply to the tumour, the findings obtained by us do not support the view that uptake of BLM by the tumour is dependent on blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide is converted by hepatic microsomal enzymes into the active metabolite, aldophosphamide, which is further converted to carboxyphosphamide by a soluble enzyme thought to be aldehyde oxidase GRAUL et al, 1967;RAUEN and KRAMER, 1964). Cyclophosphamide is converted by hepatic microsomal enzymes into the active metabolite, aldophosphamide, which is further converted to carboxyphosphamide by a soluble enzyme thought to be aldehyde oxidase GRAUL et al, 1967;RAUEN and KRAMER, 1964).…”
Section: Antagonistic Drug Interactionsmentioning
confidence: 99%